A patient-centered qualitative evaluation of meaningful change on the NSAA and PUL in Duchenne Muscular Dystrophy - Gillman, Aviva; Ciobanu, Teofil; Barrett, Louise; Davies, Evan W.; Murphy, Alexander P.; Johnson, Alex; Mills, Jessica; Heinrich, Phoebe; Przydzial, Krystian; Ewens, Bethany; Vandenberg, Gerrit; Cano, Stefan; et al. (Frontiers in Neurology, 2025)
BackgroundDuchenne Muscular Dystrophy (DMD) is a rare X-linked genetic disorder caused by mutations in the dystrophin gene. The North Star Ambulatory Assessment (NSAA) and Performance of Upper Limb (PUL) are used to measure motor performance in ambulatory and non-ambulatory individuals, respectively. There is limited published qualitative evidence on what constitutes a meaningful change on either instrument. The aim of this study is to understand meaningful change in functional abilities as measured by the NSAA and PUL at different ability levels from the perspective of individuals with DMD, caregivers of individuals with DMD, and clinicians.MethodsThe study utilized a non-interventional, descriptive, cross-sectional qualitative design consisting of 69 semi-structured interviews, including individuals with DMD (n = 18), caregivers of individuals with DMD (n = 51), and neuromuscular physiotherapists (n = 2) to understand meaningful change on the NSAA and PUL.ResultsThe results for both instruments indicated that: (i) items that are meaningful differ based on ability level; (ii) maintaining function in lower and upper limbs is the ultimate goal; (iii) meaningful change is often reported in relation to gain or loss of specific function, as opposed to number of total points on the scale; and (iv) losing one scale point corresponds to either a partial or full loss in function and activity, which has differing impacts on daily life.ConclusionThe perception of meaningful change in DMD as measured by the NSAA is influenced by ability levels and ambulatory function, with participants describing their need to maximize certain abilities, maintain function, and retain independence. For the PUL, participants underscored the importance of maintenance of their functional abilities, and highlighted key themes related to maintaining independence in ADLs, reaching, eating/drinking, and finger function for technology use across score categories.